2021
DOI: 10.1084/jem.20211327
|View full text |Cite
|
Sign up to set email alerts
|

Identification of conserved SARS-CoV-2 spike epitopes that expand public cTfh clonotypes in mild COVID-19 patients

Abstract: Adaptive immunity is a fundamental component in controlling COVID-19. In this process, follicular helper T (Tfh) cells are a subset of CD4+ T cells that mediate the production of protective antibodies; however, the SARS-CoV-2 epitopes activating Tfh cells are not well characterized. Here, we identified and crystallized TCRs of public circulating Tfh (cTfh) clonotypes that are expanded in patients who have recovered from mild symptoms. These public clonotypes recognized the SARS-CoV-2 spike (S) epitopes conserv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 58 publications
(64 reference statements)
0
42
0
Order By: Relevance
“…Recent studies sampling draining LN sites from participants immunized with Pfizer/BioNTech BNT162b2 mRNA COVID-19 vaccine demonstrated that antigen presentation in GCs occurs over months and is likely a result of sustained and robust Tfh cell responses ( Turner et al., 2020 , 2021 ; Kim et al., 2022 ; Mudd et al., 2022 ). In another study, expanded public TCRs from circulating Tfh (cTfh) clonotypes were found in patients recovering from mild COVID-19 symptoms ( Lu et al., 2021 ). The corresponding SARS-CoV-2 spike epitope was conserved across variants, presented by multiple HLAs.…”
Section: Adaptive Respiratory Immune Response: Priming Antigen-specif...mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies sampling draining LN sites from participants immunized with Pfizer/BioNTech BNT162b2 mRNA COVID-19 vaccine demonstrated that antigen presentation in GCs occurs over months and is likely a result of sustained and robust Tfh cell responses ( Turner et al., 2020 , 2021 ; Kim et al., 2022 ; Mudd et al., 2022 ). In another study, expanded public TCRs from circulating Tfh (cTfh) clonotypes were found in patients recovering from mild COVID-19 symptoms ( Lu et al., 2021 ). The corresponding SARS-CoV-2 spike epitope was conserved across variants, presented by multiple HLAs.…”
Section: Adaptive Respiratory Immune Response: Priming Antigen-specif...mentioning
confidence: 99%
“…The corresponding SARS-CoV-2 spike epitope was conserved across variants, presented by multiple HLAs. The SARS-CoV-2 epitope also activated these public cTfh clonotypes in both patients with mild symptoms and healthy donors, suggesting a more universal nature, which may be an important component of vaccines specifically eliciting T cell responses ( Lu et al., 2021 ). Sustained antigen presentation, however, is not conserved following all vaccinations or vaccine types.…”
Section: Adaptive Respiratory Immune Response: Priming Antigen-specif...mentioning
confidence: 99%
“…HLA-DRA-DRB1*15:01S 870-878 and HLA-DPA* 0103-DPB1*04S 167-180 are the most dominant SARS-CoV-2-specific CD4 + T cell epitopes described so far with known HLA restrictions in COVID-19 patients and vaccinees. 26,27 S 870-878 and S 167-180 were identified using variations of ''reverse epitope discovery,'' wherein T cell receptors of interest are first isolated and then used to map the identity of specific epitopes. Overall, there is now enough evidence to show that T cells play a role in limiting COVID-19 severity and recovery from SARS-CoV-2 infection, especially in immunosuppressed individuals lacking B cells/antibodies.…”
Section: T Cell Responses During Acute Sars-cov-2 Infectionmentioning
confidence: 99%
“…Indeed, identification of T cell clonotypes reactive to SARS-CoV-2 antigens has led to the development of a novel diagnostic test for SARS-CoV-2 authorized for emergency use by the US Food and Drug Administration (FDA). 19 In order to identify TCR repertoire signatures related to COVID-19, multiple groups have utilized either bulk TCR repertoire sequencing methods, 3,[20][21][22][23][24] which quantitatively measure the frequencies of large numbers of unpaired TCR alpha or beta chain clonotypes, or single-cell TCR-sequencing techniques, 1,2,[25][26][27][28][29][30][31] which produce fewer but paired alpha/beta TCR sequences. One of the major challenges of TCRsequencing approaches is that only a small fraction of total peripheral T cells recognize viral epitopes, even at the peak of anti-SARS-CoV-2 immune responses.…”
Section: Introductionmentioning
confidence: 99%